Assessment of supplier quality performance of computer manufacturing industry by using ANP and DEMATEL. Issue 1 (12th January 2015) - Hu, Hsiu Yuan; Chiu, Shao-I; Yen, Tieh-Min; Cheng, Ching-Chan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to establish an integrated model of Analytic Network Process (ANP) and Decision-Making Trial and Evaluation Laboratory (DEMATEL), to assist enterprises to process supplier quality performance rating and comparison and find the core improvement direction to create the value of all supply chain members. Design/methodology/approach – This study used the integrated model to process supplier quality performance rating and comparison, which not only improved the order-winners and qualifiers and continued to increase supplier quality performance, but resolved the complex and difficult cause-effect relation issue to find out core improvement items. The cases of Taiwanese industrial computer manufacturers were used to describe the application and benefits of this methodology. Findings – The results recommended that the improvement item of supplier A shall focus on design and quality conformance. The recommended improvement item and order for supplier B is design, delivery reliability and delivery speed. This study established ANP and DEMATEL evaluation models, and expanded the application field in the supplier performance evaluation. Originality/value – The ANP model is used to calculate the importance of the evaluation criteria, and the DEMATEL method is introduced to consider the impact of the casual relationship of evaluation items and to adjust the importance of the evaluation item, and to solve the complex and difficult practical causation issue.